Significance of heat transfer in coupled MHD hybrid nanofluid over a surface embedded in porous medium with thermal radiation and viscous dissipation - Rehman, Ali; Saad, Abdullah Aziz; İnç, Mustafa; Abas, Siti Sabariah; Khashi’ie, Najiyah Safwa; Rezapour, Shahram; Sudarmozhi, K. (Elsevier B.V., 2026)
This research studies the enhancement of heat transfer due to thermal radiation and viscous dissipation over a permeable and stretching surface of a two-dimensional porous medium, using a two-dimensional steady MHD hybrid nanofluid (HNF) flow model containing MWCNT-SWCNT-Cu-TiO2 nanoparticles in kerosene oil or blood. The single-nanofluid model limitations of the HNF model arise from its enhanced thermal conductivity and thermal stability. The governing partial differential equations are reduced to ordinary differential equations using the similarity method and solved semi-analytically with BVPh 2.0 due to improved convergence. Results show that the Lorentz force due to the magnetic field reduced velocities by 30–40 %. This also caused thermal boundary layer thickness to increase, while heat radiation (Rd=0–3) and Eckert’s (Ec=0–1.5) dissipation increased temperatures by 25–35 % and Nusselt numbers to increase to 2.49. In a porous medium with a porosity parameter (?=0.1–0.9), the Darcy drag effect reduces the skin-friction peak to 1.61 and improves the heat-momentum transfer rates with suction/injection. The nanofluid volume fraction ?= 0.01–0.1 increased the drag and transfer coefficients. The novelties are the dual-base, four-nanoparticle, HNF model, with the first and only known interaction among porosity-MHD-radiation, and the absence of research on steady stagnation or an impermeable sheet. The results are applicable to porous fins in nuclear coolers (velocity stabilisation), solar collectors (radiation utilisation), electronics (microchannels), and biomedical stents (blood flow control), yielding 20–50 % improvements over conventional fluids. BVPh results support real-time thermal systems engineering with a residual of < 1 % after 25 iterations. © 2026 The Authors.
Keywords: MWCNT,SWCNT,Cu,TiO2, Homotopy analysis method; Nonlinear systems; Permeable surface; Thermal radiation